Gen Z's Perception of the Application of the Presidential Election Result Recapitulation Information System in Surabaya - Erika Zahra Fitriananta; Moch Iqbal Nasrulloh Al Amin; Benedikta Ngamul; Putri Nadiatus Shofiyah; Artanti Indrasetianingsih (The Journal of Society and Media, 2025)
Democracy is a system of government that emphasises the principles of justice and equality for all citizens. One form of democratic activity is general elections. General elections are a democratic process in which citizens elect representatives or government officials through their voting rights, one of which is to elect representatives of the president and vice president. In the 2024 General Election, Gen Z voters played a significant role. The vote count utilised the Recapitulation Information System, an IT-based application for publishing and recapitulating election results. This research is based on primary data from questionnaires distributed to Gen Z participants in Surabaya City. The variables used in this research consist of 1 dependent variable, the level of trust in SIREKAP, and nine independent variables, including gender, age, education, occupation, use of the Sirekap application, information transparency, political involvement, digital literacy level of the KPU application, and political insight. Based on the results of data analysis using binary logistic regression, it is concluded that simultaneously and partially only the variables of gender, use of the Sirekap application, information transparency, political involvement, and literacy level significantly affect the level of trust in the Sirekap application, with a classification accuracy of 82.9%.